Students’ Perceptions of Teachers’ Use of Bahasa Indonesia in the English Classroom: A Case Study at SMA Fransiskus 2 Jakarta - Sibarani, Clara (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2019)
The use of the first language in the teaching and learning process is often found in English as a foreign language (EFL) classes. In Indonesia, Bahasa Indonesia is also employed in many English classes. This might bring both advantages and disadvantages to the students. This study aimed to find out the students’ perceptions toward teachers’ use of Bahasa Indonesia in the English classroom. The research employed an explanatory sequential mixed methods design and administered a questionnaire to collect the quantitative data and an open-ended interview to gain the collective data. The participants were 60 students of SMA Fransiskus 2 Jakarta. The findings revealed that most participants perceived the use of Bahasa Indonesia in their English classes positive.